The Emergence of a New 'Socialist' Market Labour Regime in China - Jutta Hebel; Günter Schucher (German Institute of Global and Area Studies (GIGA), 2006)
China's transition to a market economy has been a process of basic institutional changes and institution building. The institutional change from a socialist labour regime (SLR) as one of the backbones upholding the traditional leninist system to a new 'socialist' market labour regime (SMLR) became particularly important for the success of economic and political reforms. This analysis is based on the analytical framework of regimes and makes use of the idea of path dependence. An ensemble of institutions, mutually interconnected and influencing each other, forms the regime and shapes its trajectory. Six institutions are identified to constitute the employment regime: (1) the system of social control, (2) the production system, (3) the system of industrial relations, (4) the welfare system, (5) the family order, and (6) the educational system. The SMLR is still characterised by its socialist past and differs from other varieties of transformation labour regimes and bears little resemblance to labour regimes in Western market economies. – – Die Entstehung einer Marktwirtschaft in der VR China ist ein tief greifender Prozess institutionellen Wandels. Der Wandel von einem sozialistischen Beschäftigungsregime, das zu den Stützen des traditionellen leninistischen Systems gehörte, hin zu einem neuen 'sozialistischen' marktwirtschaftlichen Beschäftigungsregime ist dabei von besonderer Bedeutung für den Erfolg der wirtschaftlichen und politischen Reformen. Für die Analyse dieses Prozesses wird in diesem Paper der Regimeansatz vorgeschlagen, der das weitgehend national verfasste Beschäftigungsregime als ein Ensemble von Institutionen auffasst, die miteinander verbunden sind und sich gegenseitig beeinflussen. Sechs Institutionen werden betrachtet: (1) das System sozialer Kontrolle, (2) das Produktionssystem, (3) das System der Arbeitgeber-Arbeitnehmer-Beziehungen, (4) das Wohlfahrtssystem, (5) das Haushaltssystem und (6) das Bildungssystem. Das so konstitutierte Beschäftigungsregime entwickelt eine Eigendynamik mit pfadabhängigen Wandlungsmustern. Die 'sozialistische' marktwirtschaftliche Ordnung trägt daher immer noch Züge der sozialistischen Vergangenheit und unterscheidet sich von den Beschäftigungsregimen anderer Transformationsländer und westlicher Marktwirtschaften.
Keywords: B52; J08; J40; P36; 330; China; institutional change; transition; labour market; employment regime; path dependence; Arbeitsmarktpolitik; Systemtransformation; Institutioneller Wandel; Pfadabhängigkeit; Arbeitsbeziehungen; China